Dietary niche variation and its relationship to lizard population density. (2nd November 2017) - Novosolov, Maria; Rodda, Gordon H.; Gainsbury, Alison M.; Meiri, Shai
Abstract: Insular species are predicted to broaden their niches, in response to having fewer competitors. They can thus exploit a greater proportion of the resource spectrum. In turn, broader niches are hypothesized to facilitate (or be a consequence of) increased population densities. We tested whether insular lizards have broader dietary niches than mainland species, how it relates to competitor and predator richness, and the nature of the relationship between population density and dietary niche breadth. We collected population density and dietary niche breadth data for 36 insular and 59 mainland lizard species, and estimated competitor and predator richness at the localities where diet data were collected. We estimated dietary niche shift by comparing island species to their mainland relatives. We controlled for phylogenetic relatedness, body mass and the size of the plots over which densities were estimated. We found that island and mainland species had similar niche breadths. Dietary niche breadth was unrelated to competitor and predator richness, on both islands and the mainland. Population density was unrelated to dietary niche breadth across island and mainland populations. Our results indicate that dietary generalism is not an effective way of increasing population density nor is it result of lower competitive pressure. A lower variety of resources on islands may prevent insular animals from increasing their niche breadths even in the face of few competitors. Abstract : This study focuses on the relationship between population density and species dietary niche breadth when compared between islands and mainland species. This relationship has long been hypothesized to be positive on islands. However, the authors show that this relationship does not exist for island lizards. Moreover, they show no increase in dietary niche width in islands lizards. This is contrary to general accepted relationships. Those results give ground to farther study on how lizards adapt to island environments. The photo shows a species of chameleon in Madagascar catching a cricket for lunch. Photo taken by Maria Novosolov.